Preparation of Carboxyl Group Functionalized Magnetite Nanoparticles with High Magnetization - Quang Hung, Nguyen; Viet Cuong, Nguyen; Van Thang, Tran; Thi Kieu Nguyen, Hoang (Asian Journal of Chemistry, 2014)
A new route of the emulsifier-free emulsion polymerization was performed to prepare surface-functionalized magnetic nanoparticles. The Fourier transform infrared spectroscopy (FTIR) and transmission electron microscopy images confirm the formation of poly methacrylic acid (PMAA) layers and the existence of free carboxylicacid groups on the surface of magnetite particles. The poly methacrylic acid layer thickness which is estimated by thermal gravity analysis (TGA) increases from 6.5 to 10.6 nm with increasing mass ratio of monomer to magnetite from 3/1 to 16/1. The increase in thickness of the polymer cover results in the decrease in magnetization saturation of polymeric coated magnetic particles. However this reduction of about 20 emu g-1 is impressive lower compared to that in the other studies with the presence of surfactants or emulsifiers.